1999
DOI: 10.1086/313469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Categorization of Extraintestinal Nontyphoidal Salmonella Infections in Infants and Children

Abstract: The study included 172 patients, aged 0-15 years, for whom at least 1 nonfecal, nonurinary specimen was culture-positive for nontyphoidal Salmonella. Ninety-five percent had positive blood cultures. Immunocompromising diseases were found in 19% of 74 infants and 77% of 98 children. Associations between the study factors and outcomes, as localized infection or death, were assessed by logistic regression analysis. Thirty-three patients had localized infections. An adjusted risk factor for development of localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 16 publications
0
30
1
Order By: Relevance
“…Underlying immunosuppression should be ruled out in patients presenting with non-typhoidal Salmonella bacteremia in the absence of gastroenteritis [22]. A recent study of extra-intestinal non-typhoidal Salmonella infections in infants (< one year) and children up to 15 years of age showed that immunocompromised states resulting from therapy for malignancies, corticosteroid use, and severe malnutrition as a consequence of congenital heart disease or chronic pulmonary disease were associated with increased mortality rates [92].…”
Section: Enteric Infectionsmentioning
confidence: 99%
“…Underlying immunosuppression should be ruled out in patients presenting with non-typhoidal Salmonella bacteremia in the absence of gastroenteritis [22]. A recent study of extra-intestinal non-typhoidal Salmonella infections in infants (< one year) and children up to 15 years of age showed that immunocompromised states resulting from therapy for malignancies, corticosteroid use, and severe malnutrition as a consequence of congenital heart disease or chronic pulmonary disease were associated with increased mortality rates [92].…”
Section: Enteric Infectionsmentioning
confidence: 99%
“…Most cause uncomplicated gastroenteritis, and antimicrobial treatment is usually unnecessary (1). However, invasive infections requiring antibiotics occasionally occur in children, particularly in infants (30). In a previous study, we found that the incidence of bacteremia was 7.6% among pediatric patients with Salmonella-induced enterocolitis and an even higher 11.5% among infants of Ͻ3 months of age (20).…”
mentioning
confidence: 97%
“…The results reported by van der Velden et al indicate that ompR and a functional SPI-2-encoded type III protein secretion apparatus are required for delayed induction of apoptosis (32). The survival in phagocytes is an important step to induce septicemia in pigs, causing clinical signs similar to those in humans (16,31); therefore, this animal model may be used to study human salmonellosis. Salmonella is able to survive and replicate in phagocytic cells, and this is an essential component of the virulence of these bacteria (1).…”
mentioning
confidence: 98%